2015
DOI: 10.1016/j.jfda.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-pressure homogenization preparation on mean globule size and large-diameter tail of oil-in-water injectable emulsions

Abstract: The effect of different high pressure homogenization energy input parameters on mean diameter droplet size (MDS) and droplets with > 5 μm of lipid injectable emulsions were evaluated. All emulsions were prepared at different water bath temperatures or at different rotation speeds and rotor-stator system times, and using different homogenization pressures and numbers of high-pressure system recirculations. The MDS and polydispersity index (PI) value of the emulsions were determined using the dynamic light scatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…Homogenization pressure and cycle play important roles in particle size and distribution of emulsions. Figure (A) shows the decreasing trend of particle size of primary emulsions with increasing homogenization pressure, which is in agreement with the results of others . The increasing homogenization pressure raised the intensity of turbulence, cavitation and hydraulic shear forces inside the homogenization chamber, when a smaller particle size of primary emulsion was achieved .…”
Section: Resultssupporting
confidence: 90%
“…Homogenization pressure and cycle play important roles in particle size and distribution of emulsions. Figure (A) shows the decreasing trend of particle size of primary emulsions with increasing homogenization pressure, which is in agreement with the results of others . The increasing homogenization pressure raised the intensity of turbulence, cavitation and hydraulic shear forces inside the homogenization chamber, when a smaller particle size of primary emulsion was achieved .…”
Section: Resultssupporting
confidence: 90%
“…A small PDI of 0.2 indicates a narrow and concentrated particle size distribution and thus better stability against destabilization. 29,30 For parenteral application, PDI value up to 0.250 was acceptable. 31 In the present study, the particle size analysis (Table 2) confirmed that the particle diameter of CLN was within the submicron range with the average reading of ~100 nm.…”
Section: Characterizations Of Clnmentioning
confidence: 96%
“…Globule size and size distribution depend upon a number of factors including, formulation design, selection of oil phase, selection of surfactant, mechanical stirring, and also on the container of the emulsion . Mechanical stirring or surfactant or both are major factors responsible to produce an emulsion with fine globule size and narrow size distribution …”
Section: Methodsmentioning
confidence: 99%